2019
DOI: 10.1021/acsami.9b09677
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Manganese Oxide Getter for Capturing Airborne Cr and S Contaminants in High-Temperature Electrochemical Systems

Abstract: Traces (ppm to ppb level) of airborne contaminants such as CrO2(OH)2 and SO2 irreversibly degrade the electrochemical activity of air electrodes in high-temperature electrochemical devices such as solid oxide fuel cells by retarding oxygen reduction reactions. The use of getter has been proposed as a cost-effective strategy to mitigate the electrode poisoning. However, owing to the harsh operating conditions (i.e., exposure to heat and moisture), the long-term durability of getter materials remains a considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The LSCF particle surface has numerous nano-bumps indicative of Sr exsolution (Figure 5A), which was not initially present (Figure 6B). The nano-bumps are likely to be sulfur compounds such as SrSO 4 , based on previous research (Hong et al, 2019). Correspondingly, as can be seen in Figure 5B, the EDS spectrum from the LSCF particle with the surface nanoparticles (Region 2), shows a higher sulfur concentration than that from the LSCF particle core (Region 1).…”
Section: Structural Modification Of Lscf and Lsm In Cyclic Conditionssupporting
confidence: 56%
See 1 more Smart Citation
“…The LSCF particle surface has numerous nano-bumps indicative of Sr exsolution (Figure 5A), which was not initially present (Figure 6B). The nano-bumps are likely to be sulfur compounds such as SrSO 4 , based on previous research (Hong et al, 2019). Correspondingly, as can be seen in Figure 5B, the EDS spectrum from the LSCF particle with the surface nanoparticles (Region 2), shows a higher sulfur concentration than that from the LSCF particle core (Region 1).…”
Section: Structural Modification Of Lscf and Lsm In Cyclic Conditionssupporting
confidence: 56%
“…The LSM particles appear to have smooth surfaces with no evidence of Sr exsolution and SrSO 4 formation (Figure 8A). It should be noted that in our previous study (Hong et al, 2019), an LSM|YSZ cell, exposed to 4 ppm SO 2 for 120 h but without subsequent exposure to air flow, has sulfur-enriched nanoparticles (regarded as SrSO 4 ) protruding on the surface. It is thus indicated that, in the subsequent air flow, the sulfur physi/chemisorbed on the LSM surface is released while the strontium is partially dissolved back into LSM.…”
Section: Structural Modification Of Lscf and Lsm In Cyclic Conditionsmentioning
confidence: 86%
“…For instance, SrCO 3 nanowhiskers were found to grow from Sr 4 Mn 3 O 10 in humid environment (see Supplementary Fig. S4 online), which have potential applications as Cr/S getters 43 in high-temperature electrochemical systems. While water molecules are considered contributors to the directional growth, the role of water molecules in Sr carbonation is rarely studied.…”
Section: Resultsmentioning
confidence: 99%
“…Borosilicate glass sealants have also been modified with B-stabilizing dopants to form borates, but completely mitigating B volatility remains a challenge (38,39). Recently, sacrificial and cost-effective 'getters' have been proposed and demonstrated as a method to capturing SO2 and Cr vapor contaminants with before reaching electrochemically sensitive components (40,41,42). Based on basic alkaline-earth metals, the getter's affinity for acidic CO2(g), SO2(g), Si(OH)4(g), H3BO3(g) and CrO2(OH)2(g) makes them capable of scrubbing contaminated air, preserving solid oxide cell performance (42,43).…”
Section: Introductionmentioning
confidence: 99%